Free convection boundary layer flow of viscoelastic micropolar fluid past a horizontal circular cylinder - Laila Amera, Aziz; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; Sharidan, Shafie (2018)
This study intends to observe the behaviour of the flow of viscoelastic micropolar fluid under boundary layer approximation moving over a horizontal circular cylinder at constant wall temperature. First, a set of governing equations is formulated before they are transformed into dimensionless form. Stream function is then applied to the obtained equations, producing sets of partial differential equations which are then solved numerically using a finite difference scheme, namely the Keller-box method. The skin friction and heat transfer characteristics of the flow are observed at multiple values of viscoelastic parameter, K, material parameter, K1, and the magnetic parameter, M.